Synthesis of liquid menthol by hydrogenation of dementholized peppermint oil over Ni catalysts - Manuale, Débora Laura (2010)
Hydrogenation of (-)-menthone and (+)-isomenthone was studied at 2.7 MPa and 100 °C. The objective was to produce a liquid menthol mixture rich in (-)-menthol from dementholized peppermint oil. Ni-based catalysts were tested and compared for this reaction: a) 6 and 12% Ni dispersed into a nonstoichiometric magnesium aluminate (Ni-Mg-Al) with spinel structure; b) Ni-Raney catalyst. Both types of catalysts were active for (-)-menthone and (+)-isomenthone hydrogenation. Lower conversion but higher selectivity to (-)-menthol was obtained with Ni-Mg-Al catalysts. However, they rapidly lost their activity. Instead Ni-Raney catalysts kept its original activity even after several hydrogenation runs.